Impact of Audit Committee on the Association Between Financial Reporting Quality and Shareholder Value - Karajeh, Ahmad Ibrahim; Ibrahim, Mohd Yussoff B. (International Journal of Economics and Financial Issues, 2017)
Regulatory and governmental authorities in Malaysia provide substantial financial planning to help attract potential investors and improve value for shareholders. Companies are always encouraged to improve the quality of financial reporting. However, some managers tend to manipulate earnings’ data to make it appear more attractive. Stakeholders rely on the audit committee to motivate managerial provision of accurate data for accounting processes. Hence, this study examines the impact of financial reporting quality on shareholder value and assesses impacts from the audit committee’s influence and its relationship to financial reporting. The proposed study will use modified Jones Model to evaluate the financial reporting quality. Also, the study proposes ordinary least square (OLS) for identifying the impact of (i) independent audit committee; (ii) financial and accounting expertise; and (iii) audit committee size as proxies to investigate the effect of the audit committee on the relationship between financial reporting quality and shareholder value. Keywords: Financial Reporting Quality, Shareholders’ Value, Audit Committee. JEL Classifications: M41, M42, G1